Template Analysis of a Longitudinal Interprofessional Survey: Making Sense of Free-Text Comments Collected Over Time - Brown, Melanie; Pullon, Sue; McKinlay, Eileen; Gray, Lesley; Darlow, Ben (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2022)
Surveys are widely used in interprofessional education (IPE) research and these often collect free-text data. The potential contribution of free-text data to analysis and interpretation is often missed through separate reporting of qualitative and quantitative results, or free-text analyses being superficial or limited to subsets of data. There is little published guidance on how to maximize the use and integration of free-text comments with quantitative responses in large datasets collected over multiple years. Analysis of all qualitative comments, within the context of their related quantitative answers, enables exploration of changes in participants’ construction of meaning over time. This article describes how we used template analysis to analyze 3,626 free-text responses, collected as part of a five-year survey exploring the impact of an IPE program on health professionals’ attitudes to teamwork and early careers. We outline the main procedural steps undertaken by a team of researchers and we share our insights into the methodological challenges encountered. This article aims to inspire other researchers at the planning stage of research proposals, and assist them with practical ideas during data extraction, management, analysis, and reporting of large free-text datasets. We conclude that template analysis has methodologically sound, pragmatic utility in IPE longitudinal survey research.